2013
DOI: 10.1097/inf.0b013e31829479d3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Respiratory Syncytial Virus Prophylaxis Based on Predetermined Dates Versus Regional Surveillance Data

Abstract: The provincial prophylactic period aligned with the local fixed-date and prospective methods. However, the adoption of any of the first 2 strategies merits close observation to minimize excess healthcare expenditure. The prospective surveillance of laboratory isolates should be further explored as a preferred option to better define prophylactic periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…In these cases, immune prophylaxis with monthly injections of palivizumab is recommended during the RSV season [ 7 ]. Early initiation of immune prophylaxis increases the costs, as more than five doses are necessary to protect a child for the whole season, while a late initiation leave them unprotected during the beginning of the season [ 8 ]. There are geographical variations at the start and end of the outbreak and understand them can help optimize immune prophylaxis strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, immune prophylaxis with monthly injections of palivizumab is recommended during the RSV season [ 7 ]. Early initiation of immune prophylaxis increases the costs, as more than five doses are necessary to protect a child for the whole season, while a late initiation leave them unprotected during the beginning of the season [ 8 ]. There are geographical variations at the start and end of the outbreak and understand them can help optimize immune prophylaxis strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The presumed start of the RSV season, and the start of prophylaxis with palivizumab, is often set by regional healthcare authorities based on historical data in those areas. A recent analysis of Canadian data found that the most effective method of determining the start of the RSV season was through the surveillance of virology data from local laboratories, assuming a 2-day turnaround in laboratory results [ 28 ]. In Ireland and the Netherlands, the RSV season usually extends from September/October through March/April and palivizumab prophylaxis typically begins in early October.…”
Section: Rsv Prophylaxis Overviewmentioning
confidence: 99%
“…Besides therapeutic treatment, another possible strategy in high‐risk COPD patients is prophylaxis in a household or community setting. Most acute respiratory infections, including influenza and RSV, cause seasonal epidemics during 2–4 months, and seasonal prophylaxis would be an option to prevent such infections . Drug compliance during seasonal prophylaxis may not be easily achieved in some patients, and the rather low degree of seasonality of rhinovirus infection together with the possibility of resistance development toward the drugs with a low barrier to resistance (such as capsid binders) disfavors prophylactic use.…”
Section: Which Patients Would Benefit From Anti‐rhinovirus Therapy Anmentioning
confidence: 99%